Teaching anthropology: learning to look at the world - Ramos, M.; Afonso, A. I. (EXPLORING THE PRACTICES OF ACADEMIC TEACHING AND LEARNING 08?–?09 2017 JUNI FORSCHENDES LERNEN IN ETHNOLOGIE UND KULTURWISSENSCHAFT, 2017)
The academic teaching model that is today globally pursued - and reinforced – is based on lecturing, tutoring, evaluating and seminaring practices that were originally formed in accordance with both monastic and clerical traditional forms of immuring knowledge. The world over, lecturers ritually abide to the practice of offering sermons to an expectedly obedient public of students turned clients. The widespread standardization of syllabuses and bibliographies add to a conception of the classroom as the place where canon is to be learned. There is something of a paradox in this. The coming of the digital era is clearly impacting on how academic knowledge is produced and transmitted, challenging the foundations of traditional teaching practices. But as their privileged role of knowledge shapers and transmitters is questioned and eroded by an overflow of readily available information, lecturers defensively tend to entrench themselves in more-of-the-same teaching practices. A creative and stimulating way out of these conundrums is to engage and involve students in the basic understanding that the classroom is a place that prepares for thinking, that thinking goes much beyond reasoning (in the sense that it is more than what written words make of reasoning, of cognizing) and that fieldwork is the place where immersive, challenging, non-standardized thinking is produced to form the specificities of anthropological knowledge. Having this in mind, then the classroom ought to become the laboratory where these problems are raised, not a place where they are dissolved, deleted or diverted. And if observation, visualization, imagination are important elements to thinking-in-the-field, than it is only sensible that this be brought to the fore in teaching anthropology. What we do with digital media (and are done by it) needs to be weighed against what we do (and are done) otherwise. It’s not that we should turn our backs to the fact of the digital era, but to understand how the analogical world impacts and is impacted by the digital world. We thus advocate that the walls between the classroom and the field be shaken, that observation practices be valued essential to teaching, and that the use of simple analogical means of recording and thinking be fostered. This means that fieldwork journals – of the type where all graphic possibilities are included – are not necessarily a complement, an eccentricity, but an essential node for anthropological knowledge.